Malaria and amphetamine 'horse tablets' in Thailand. - Newton, P; Chierakul, W; Ruangveerayuth, R; Abhigantaphand, D; Looareesuwan, S; White, N (2003)
During recent clinical malaria research in Thailand we found a high frequency of amphetamine misuse and withdrawal amongst patients admitted to hospital with Plasmodium falciparum malaria. This comorbidity may cause diagnostic confusion, alter malaria pathophysiology and lead to drug interactions.